Cu2O Hybridized Titanium Carbide with Open Conductive Frameworks for Lithium-ion Batteries. (1st June 2016) - Zhang, Huang; Dong, Hui; Zhang, Xuan; Xu, Yunlong; Fransaer, Jan
Abstract: Though MXenes, a new family of 2D transition metal carbides, are generating considerable interests as electrode materials for batteries and supercapacitors, further application is hindered by their low capacities and poor rate capabilities. Here we propose a simple route for the synthesis of Cu2 O particle hybridized titanium carbide Ti2 CTx (T = O, OH) composites via a solvothermal method. Electrodes containing Cu2 O/MXene were fabricated without carbon black, and tested as anodes for lithium ion batteries. A discharge capacity of 143 mAh g −1 was obtained at a discharge current density of 1000 mA g −1 and the capacity retention was near 100% after 200 cycles. The hybrid electrodes with open conductive frameworks exhibited significantly improved electrochemical performance, suggesting a new method for preparing MXene-based composites for energy storage application.